A Theoretical and Socio-Political Analysis of Vaccine Refusal and Its Implications in Turkey during the Covid-19 Pandemic: The Rejection of Science, Medicalization and the Conspiratorial-Populistic Discourses - Daldal, Asli; Conker, Ahmet; Nas, Cigdem (ANKARA HACI BAYRAM VELI UNIV, 2023)
The Covid-19 pandemic has revealed that the ever-increasing 'vaccine refusal' can no longer be avoided with simple public health measures. The 'vaccine refusal', which generally manifests itself as a distrust of 'scientific-medical authorities', actually seems to be related to a much broader epistemological crisis. This study aims at examining the 'vaccine refusal' from particularly philosophical and socio-political perspectives. In recent years, the rising 'postmodern' anti-scientific approaches tended to deconstruct the positivistic approaches developed during the Enlightenment and the subsequent scientific revolution. The phenomenon of globalization and the ensuing populist tendencies that feed these anti-scientific discourses are often combined with the 'politics of the body' or 'biopolitics', especially in the rise in western Europe. These developments pave the way for the irrational and sceptical approach of individuals from all walks of life towards scientific and public authorities. On the other hand, the neoliberal developments in the field of 'industrial medicine' combined with the epistemological crisis summarized above, damage the relationship of trust between the patient and the physician. It is also noticeable that vaccine refusal can also be articulated within nationalist-populist discourses, especially in Turkey. In this context, the 'conspiratorial' anti-vaccine discourses within current politics are also worth examining.
Keywords: Vaccine Refusal and Covid-19; Conspiratorial Thinking; Populism and Covid-19; The Rejection of Science; Vaccine Refusal and Industrial Medicine; Nationalism and Vaccine Refusal in Turkey; Public Administration